2013
DOI: 10.1136/oemed-2012-101212
|View full text |Cite
|
Sign up to set email alerts
|

Occupational trichloroethylene exposure and risk of lymphatic and haematopoietic cancers: a meta-analysis

Abstract: The carcinogenic potential of trichloroethylene (TCE) continues to generate much controversy, even after the US Environmental Protection Agency raised its classification to 'carcinogenic to humans'. We conducted a meta-analysis of published cohort and case-control studies exploring occupational TCE exposure in relation to five different lymphatic and haematopoietic cancers: non-Hodgkin's lymphoma (NHL, N=24), Hodgkin's lymphoma (HL, N=13), multiple myeloma (MM, N=11), leukaemia (N=12) and chronic/small lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 62 publications
2
25
0
3
Order By: Relevance
“…Based on our data, we observed an increase in risk of PTCL and, specifically, ALCL, for textile workers. Exposures related to textile work include: dust, endotoxin (a bacterial contaminant of raw cotton fiber and cotton dust), assorted dyes, and chemicals such as trichloroethylene, which has previously been linked to lymphoma risk (33)(34)(35)(36)(37)(38). We also report that electrical fitters had increased odds of developing ALCL and angioimmunoblastic lymphoma.…”
Section: Discussionmentioning
confidence: 52%
“…Based on our data, we observed an increase in risk of PTCL and, specifically, ALCL, for textile workers. Exposures related to textile work include: dust, endotoxin (a bacterial contaminant of raw cotton fiber and cotton dust), assorted dyes, and chemicals such as trichloroethylene, which has previously been linked to lymphoma risk (33)(34)(35)(36)(37)(38). We also report that electrical fitters had increased odds of developing ALCL and angioimmunoblastic lymphoma.…”
Section: Discussionmentioning
confidence: 52%
“…Karami 2013 41 Epidemiologic cohort or caseecontrol studies that presented RR estimates for International Classification of Diseases codes that corresponded to MM or leukemia or with data that allowed for the calculation of RRs for a TCE-exposed worker population (eg, TCE used as a solvent among aircraft maintenance workers) were included. Ecological studies of TCE in community drinking-water because study design issues limit their use for making causal inferences were excluded.…”
mentioning
confidence: 99%
“…Routes of exposure were unknown for these studies and cases were likely exposed via multiple routes. These authors reported a significantly raised summary estimate of non-Hodgkin's lymphoma (relative risk=1.93; CI: 1.14 to 1.54) for all cohort and case-control studies [Karami et al 2013]. Table 2 …”
Section: Systemic Toxicity From Skin Exposure (Sk: Sys)mentioning
confidence: 99%
“…inhalation, dermal, oral) is unknown [Hansen et al 2013;Karami et al 2013]. Hansen et al [2013] found increased liver cancer 1.93 times more likely (confidence interval [CI] 1.19 to 2.95) and cervical cancer 2.31 times more likely (CI: 1.32 to 3.75) in workers exposed to TCE; however, exposure routes are unknown and were likely a combination of multiple routes (inhalation and dermal).…”
Section: Systemic Toxicity From Skin Exposure (Sk: Sys)mentioning
confidence: 99%
See 1 more Smart Citation